TECHNOLOGY OF PROFESSIONAL TRAINING OF FUTURE TEACHERS BASED ON A COMPETENCE-BASED APPROACH - Ergasheva Ba’rno Ziyavitdin qizi (Лучшие интеллектуальные исследования, 2024)
Annotation: This article will talk about the competence of students of the Department of Pedagogy in the conditions of development. The content of pedagogical quality and professional training, which should be mastered for future educators, is covered.